Physalis ixocarpa Brot. ex Hornem. and Verbena litoralis Kunth, new Spanish xenophytes and records of other interesting alien vascular plants in Catalonia (Spain) - Verloove, Filip (Lazaroa, 2003)
A floristic survey of the synanthropic flora in the surroundings of Blanes (Catalonia, provinces of Barcelona and Gerona) revealed the presence of several interesting species. The present paper deals with the present distribution and degree of naturalization of ten taxa, two of them presumably new to Spain (Physalis ixocarpa y Verbena litoralis).